2023
DOI: 10.1002/cncr.34685
|View full text |Cite
|
Sign up to set email alerts
|

Desire for children among male survivors of childhood cancer: A DCCSS LATER study

Abstract: Background Knowledge of the desire for children among childhood cancer survivors (CCSs) is scarce. This study evaluated the desire for children in male CCSs in comparison with male siblings. Methods A nationwide cohort study was conducted as part of the Dutch Childhood Cancer Survivor Study LATER study: 1317 male CCSs and 407 male sibling controls completed a questionnaire addressing the desire for children. Logistic regression analyses were used to explore the independent association between survivorship stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…After treatment, survivors sometimes reconsider their life goals [11,13,66], and this study showed that almost 20% of female, but only 8% of male survivors wanted no (additional) children due to their cancer experience. This corroborates qualitative studies where mostly female survivors are concerned about relapses and their ability to have a healthy pregnancy [67][68][69][70][71].…”
Section: Reproductive Goalsmentioning
confidence: 91%
“…After treatment, survivors sometimes reconsider their life goals [11,13,66], and this study showed that almost 20% of female, but only 8% of male survivors wanted no (additional) children due to their cancer experience. This corroborates qualitative studies where mostly female survivors are concerned about relapses and their ability to have a healthy pregnancy [67][68][69][70][71].…”
Section: Reproductive Goalsmentioning
confidence: 91%
“…Unfortunately, male survivors of childhood cancer have a higher desire for children compared with their siblings (25% vs . 7%) ( 4 ), thereby developing interventions that preserve male fertility is a necessity for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the Dutch cohort of CCSs, three-quarters of 1317 male survivors reported to have a desire for children. 5 Because many young adults place great importance on fertility, the potential for infertility can cause significant emotional distress. 6 Ongoing research that focuses on evaluating the toxicity risk of various chemotherapeutic agents and radiotherapy schedules on gonadal function will support personalized infertility risk assessment and guidance on options for fertility preservation at cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the Dutch cohort of CCSs, three‐quarters of 1317 male survivors reported to have a desire for children 5 . Because many young adults place great importance on fertility, the potential for infertility can cause significant emotional distress 6 .…”
Section: Introductionmentioning
confidence: 99%